Use of Cumulative Assessments in U.S. Schools and Colleges of Pharmacy - Deepti Vyas; Jenana Halilovic; Myo-Kyoung Kim; Marcus C. Ravnan; Edward L. Rogan; Suzanne M. Galal (MDPI AG, 2015)
The Accreditation Council of Pharmacy Education (ACPE) has taken a strong stance on assessment in pharmacy education. One available assessment tool is cumulative assessments, which may be administered at various points in the curriculum. This article presents the results of a survey of U.S. schools of pharmacy regarding the use of cumulative assessments within their curriculum. A 20-question survey tool was emailed to 125 schools of pharmacy. A total of 105 out of 125 schools participated (response rate 84%). Of these, 52 schools currently have a cumulative assessment program; 18 have one cumulative exam prior to advanced pharmacy practice experiences (APPEs); 19 have a cumulative exam every didactic year; and seven have accumulative exams every semester, except during APPEs (n = 44). Increased faculty workload emerged as the top challenge faced by schools that have implemented a cumulative assessment program. Eighteen schools indicated that no outcomes are measured to determine the utility of the cumulative assessment. From these results, it appears that almost half of participating U.S. schools have implemented a cumulative assessment plan. However, it is apparent that more research needs to be done to determine which outcomes are expected to improve with the implementation of such an assessment plan.